Postconflict affiliation among bystanders in a captive group of japanese macaques (Macaca fuscata) - Daniel, João Rodrigo (2015)
Social animals benefit from group living. However, competition for limited resources may lead to agonistic conflicts. These conflicts can affect the behavior and the social relationships, not only of the individuals involved in the confrontation, but also of bystanders. The aim of this study was to describe postconflict affiliative interactions among bystanders (quadratic affiliation) in a captive group of Japanese macaques (Macaca fuscata) and test whether 1) after observing a conflict bystanders tend to interact with other bystanders, 2) conflicts increase bystanders’ rates of selfdirected behaviors (SDBs), 3) postconflict rates of SDBs mediate affiliative interactions between bystanders, and 4) quadratic affiliation decreases rates of SDBs to baseline levels. We used the postconflict matched-control (PC-MC) method (5 min focal samples) to record bystanders’ behavior (156 PC-MC pairs from 15 subjects). Results show that bystanders’ rates of SDBs increased above baseline levels after conflicts. Bystanders responded to conflicts by increasing affiliation with other bystanders (mainly with close associates) but not with former combatants. After quadratic affiliation, rates of SDBs decreased to baseline levels. Together with previous findings, these results support the idea that quadratic affiliation is a tension reduction mechanism in less tolerant species.